Kaitan Beban Kerja dan Kepuasan Kerja dengan Kinerja Karyawan dan Motivasi sebagai Variabel Mediasi - Nasution, Cecilia Stephani Permatadewi; Cahyaningtyas, Sekar Esti; Sugiarti, Rini; Suhariadi, Fendy (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This study aims to determine the effect of workload and job satisfaction on employee performance at Bohopanna Semarang, using motivation as a mediation. This research employs a quantitative method. The population of this study consists of 60 employees, using a census sampling technique, meaning all members of the population are included as sample members. Data collection is conducted using questionnaires. The analysis technique used is SEM Partial Least Square (PLS). The results of this study indicate that workload has a negative and significant effect on motivation, job satisfaction has a positive and significant effect on motivation. Motivation has a positive and significant effect on performance. Workload has a negative and significant effect on performance. Job satisfaction has a positive and significant effect on performance. Motivation mediates the effect of workload and job satisfaction on performance, exhibiting partial mediation.